Systemic above- and belowground cross talk: hormone-based responses triggered by Heterodera schachtii and shoot herbivores in Arabidopsis thaliana - Kammerhofer, Nina; Egger, Barbara; Dobrev, Petre; Vankova, Radomira; Hofmann, Julia; Schausberger, Peter; Wieczorek, Krzysztof (Journal of Experimental Botany, 2015)
Above- and belowground plant parts are simultaneously attacked by different pests and pathogens. The host mediates these interactions and physiologically reacts, e.g. with local and systemic alterations of endogenous hormone levels coupled with coordinated transcriptional changes. This in turn affects attractiveness and susceptibility of the plant to subsequent attackers. Here, the model plant Arabidopsis thaliana is used to study stress hormone-based systemic responses triggered by simultaneous root parasitism by the cyst nematode Heterodera schachtii and shoot herbivory by the thrips Frankliniella occidentalis and the spider mite Tetranychus urticae. First, HPLC/MS and quantitative reverse transcriptase PCR are used to show that nematode parasitism strongly affects stress hormone levels and expression of hormone marker genes in shoots. Previous nematode infection is then demonstrated to affect the behavioural and life history performance of both arthropods. While thrips explicitly avoid nematode-infected plants, spider mites prefer them. In addition, the life history performance of T. urticae is significantly enhanced by nematode infection. Finally, systemic changes triggered by shoot-feeding F. occidentalis but not T. urticae are shown to make the roots more attractive for H. schachtii. This work emphasises the importance of above- and belowground signalling and contributes to a better understanding of plant systemic defence mechanisms against plant-parasitic nematodes.
Keywords: kořeny rostlin; Thysanoptera; rostlinné buňky; Animals; Tetranychidae; Herbivory; regulátory růstu rostlin; zvířata; Plant Growth Regulators; Plant Roots; Tylenchoidea; Cell Communication; výhonky rostlin; mezibuněčná komunikace; Plant Cells; Arabidopsis; Plant Shoots; býložravci